From this wicked patch of dust - Troncoso, Sergio, 1961- (Camino del sol., 2011)
Mexican-born Cuauhtemoc and Pilar Martinez came to America so that their children Julia, Francisco, Marcos and Ismael could make something of themselves. While the children experience different journeys, at the center lay all the love and teachings from their parents that bind them together. With El Paso and Ysleta as the backdrop (though family members also find themselves in Boston, New Mexico, Jerusalem, Iraq ...), this book offers a blend of short stories in chronological form to showcase the struggles of the Martinez family and explore issues of assimilation, immigration, religion, politics and war.